PBI UMY Students’ Critical Reading Levels - Abdul Rasyid Ghazali (PBI 15 UMY 029, 2015)
*29 Despite the importance of critical reading, English Education Department (PBI) Universitas Muhammadiyah Yogyakarta (UMY) did not strongly encourage its students to be critical readers. In fact, the majority of PBI lecturers only gave assignments to read text books and understand their contents, but, analyzing and giving arguments toward reading texts were rarely applied. The critical reading term refers to students’ activities in reading which include analyzing, reflecting, and evaluating texts. This study investigated students’ critical reading levels at PBI UMY. Specifically, this research focused on critical readers’ population and students’ ability in critical reading. The analyzing, evaluating, and creating levels of revised Bloom’s Taxonomy was used to classify students’ critical reading levels. In this descriptive quantitative study, 264 questionnaires were distributed, and all were returned. The respondents were PBI UMY active students from batch 2011 – 2014. SPPS 22 and Microsoft Excel were used to analyze the population of critical readers and students’ ability. The results show that 92% out of total population was critical readers, which consists of 35% students at the analyzing levels, 23% students at the evaluating levels, and 33% students at the creating levels. The study also showed that students of PBI UMY had a high ability in analyzing a reading text. Meanwhile, in evaluating text, students of PBI UMY had moderate ability. Furthermore, in creating text, students of PBI UMY had low ability